Congenital Lambert-Eaton myasthenic syndrome. Issue 4 (April 1987) - Bady, B; Chauplannaz, G; Carrier, H
Abstract : A 4 year old girl had been hypotonic and areflexic since birth with delayed milestones in motor development. Repetitive stimulation at high rates performed at 3 years elicited an incremental response typical of the Lambert-Eaton Syndrome.